Controlled synthesis of gold nanorod dimers with end-to-end configurations. Issue 21 (5th May 2022) - Lu, Xuxing; Punj, Deep; Orrit, Michel
Abstract : End-to-end gold nanorod dimers provide unique plasmonic hotspots with extremely large near-field enhancements in the gaps. Abstract : End-to-end gold nanorod dimers provide unique plasmonic hotspots with extremely large near-field enhancements in the gaps. Thereby they are beneficial in a wide range of applications, such as enhancing the emissions from ultra-weak emitters. For practical purposes, synthesis of gold nanorod dimers with high yield, especially on the substrates, is essential. Here, we demonstrate two controllable strategies to synthesize gold nanorod dimers based on the self-assembly of gold nanorods, either in bulk solution or on the surface of a glass substrate directly. Both methods can give a high yield of gold nanorod dimers, yet, assembling them directly on the substrate provides more flexibility in controlling the shape and size of each nanorod within the dimer. We also show that these gold nanorod dimers can be used to enhance two-photon-excited fluorescence signals at the single-molecule level.